Navigating Globalization: Reforming Islamic Education for the 21st Century - Hajar, Andi (Sinergi International Journal of Islamic Studies, 2024)
Islamic education is at a pivotal crossroads as globalization accelerates the need for comprehensive educational reform across Muslim-majority societies. This narrative review investigates how Islamic educational institutions are adapting to global influences while maintaining fidelity to religious values. Employing a structured literature review of sources from Scopus, Google Scholar, and PubMed, this study analyzes academic works published over the past 15 years. Keyword combinations including "Islamic education," "globalization," and "educational reform" guided the search and selection criteria. The review identifies critical themes related to curriculum innovation, teacher and leadership roles, technological integration, and regional adaptation strategies. Findings indicate that educational institutions integrating global competencies with Islamic values tend to exhibit higher adaptability, especially in Southeast Asia. Teachers and school leaders play transformative roles in aligning pedagogical strategies with modern educational standards, while digital tools have enhanced learning access and quality. However, systemic challenges related to policy gaps, funding disparities, and infrastructural constraints persist. Comparative insights from regions such as the Middle East and Africa reveal varied approaches and underscore the importance of contextualized reform. The review concludes that successful reform hinges on institutional resilience, inclusive policymaking, and the integration of technological innovation. These strategies are essential to preserving the spiritual integrity of Islamic education while preparing students for global citizenship. Further empirical and comparative research is recommended to bridge current gaps and inform more inclusive reform strategies.